Pentaerythritol based push–pull tetramers for organic photovoltaics. Issue 9 (21st September 2017) - Labrunie, Antoine; Josse, Pierre; Dabos-Seignon, Sylvie; Blanchard, Philippe; Cabanetos, Clément
Abstract : We report herein the synthesis, characterization and preliminary evaluation of two simple tetramers based on the functionalization of a central pentaerythritol σ-linker with push–pull chromophores as molecular donor for organic photovoltaics. Abstract : The synthesis and characterization of two tetramers based on the functionalization of a central pentaerythritol σ-linker with push–pull chromophores is reported herein. Prepared in only few steps, these original molecules exhibit interesting optical and electrochemical properties. Moreover, once evaluated as donor materials, promising power conversion efficiencies of 4.5% were reached when blended with the [6, 6]-phenyl-C71 -butyric acid methyl ester (PC71 BM ) in bulk heterojunction solar cells.